PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2018 – 2020) - Muhammad Resha Bahtiar; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2022)
This study aims to examine and analyze the effect of the Corporate Governance mechanism on the company's financial performance with ownership structure as a moderating variable. Financial performance is calculated using ROA, while the Corporate Governance mechanism is determined by the independent board of commissioners, board of directors, and audit committee variables. Ownership structure indicators are institutional, and foreign ownershipThe sample of this research is banking companies listed on the Indonesia Stock Exchange for the period 2018-2020. The number of samples used as many as 38 companies taken through purposive sampling. The analytical method of this study uses multiple regression.Agency theory raises the concept of corporate governance in managing the company's business, corporate governance is expected to be able to deal with conflicts through monitoring the performance of agents. The results of this study indicate that corporate governance affects the company's financial performance partially and simultaneously. However, the ownership structure does not strengthen the relationship of corporate governance to the company's financial performance.